Peningkatan Kapasitas dan Kualitas Produksi UKM Busana Muslim Pria di Bungah Gresik - Muhammad Arfan Mu’ammar; Mukayyat Al-Amien (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2017)
Mitra I (UKM Songkok Three Key) produces black velvet material. Partner Part I Problem (UKK Songkok Three Keys) is limited production capacity and often damaged, not yet have production license. And overcome the management of bookkeeping, marketing, packaging, product design is still traditional so difficult to enter the Modern market and limited capital, as well as traditional business institutions. Mitra II (UKM Baju Takwa Bin Afifi) produces cotton cloth. Partner II problems are limited production capacity due to poor and often damaged production tools, product quality problems of bin Afifi are less competitive rural jobs, and issues of bookkeeping management, marketing, packaging, product design is still traditional so as not to compete with other products and limited capital, and still traditional business institutions. The purpose of this research is to develop an independent and professional partner business group. The solutions offered in this program are: the effort to increase the production capacity and the marketing management of the business, strengthening the business group institutions. Solutions offered in this program is to provide production tools, business management training and marketing, facilitate the formation of business groups in a professional, mentoring the media marketing business in technology. IbM's Outbound Program is a scientific publication on Journals with ISSN, Model promotion with online media and professional institutional arrangement of UKM.